Enhancement of electrochemical properties by polysulfide trapping in a graphene-coated sulfur cathode on patterned current collector. Issue 15 (26th January 2016) - Yu, Seung-Ho; Lee, Bora; Choi, Sinho; Park, Soojin; Hong, Byung Hee; Sung, Yung-Eun
Abstract : A sulfur cathode on a honeycomb-shape-patterned Al current collector was prepared and successfully sealed using triple-layered graphene. Abstract : A sulfur cathode on a honeycomb-shape-patterned Al current collector was prepared and successfully sealed using triple-layered graphene. Graphene layers on the sulfur cathode well confined the dissolved polysulfide in the electrode, leading to significantly enhanced electrochemical properties including cycle retention and Coulombic efficiency.